Hydrostatic pressure and muscarinic receptors are involved in the release of inflammatory cytokines in human bladder smooth muscle cells. Issue 5 (30th August 2016) - Liang, Zhou; Xin, Wei; Qiang, Liu; Xiang, Cai; Bang‐Hua, Liao; Jin, Yang; De‐Yi, Luo; Hong, Li; Kun‐Jie, Wang
Abstract : Aims: Abnormal intravesical pressure results in a series of pathological changes. We investigated the effects of hydrostatic pressure and muscarinic receptors on the release of inflammatory cytokines in rat and human bladder smooth muscle cells (HBSMCs). Methods: Animal model of bladder outlet obstruction was induced by urethra ligation. HBSMCs were subjected to elevated hydrostatic pressure and/or acetylcholine (Ach). Macrophage infiltration in the bladder wall was determined by immunohistochemical staining. The expression of inflammatory genes was measured by RT‐PCR, ELISA and immunofluorescence. Results: In obstructed bladder, inflammatory genes and macrophage infiltration were remarkably induced. When HBSMCs were subjected to 200–300 cm H2 O pressure for 2–24 h in vitro, the expressions of IL‐6 and RANTES were significantly increased. Hydrostatic pressure promoted the protein levels of phospho‐NFκB p65 and phospho‐ERK1/2 as well as muscarinic receptors. Moreover, NFκB or ERK1/2 inhibitors suppressed pressure‐induced inflammatory genes mRNA. When cells were treated with 1 μM acetylcholine for 6 h, a significant increase in IL‐6 mRNA expression was detected. Acetylcholine also enhanced pressure‐induced phospho‐NFκB p65 and IL‐6 protein expression. Additionally, pressure‐induced IL‐6 was partially suppressed by muscarinic receptors antagonists. Conclusions: Hydrostatic pressure and muscarinic receptors were involved in the secretion of inflammatory cytokines in HBSMCs, indicating a pro‐inflammatory effect of the two factors in the pathological process of BOO.